Resource-Efficient Medical Image Analysis First MICCAI Workshop, REMIA 2022, Singapore, September 22, 2022, Proceedings - Xu, Xinxing; Li, Xiaomeng; Mahapatra, Dwarikanath; Cheng, Li.; Petitjean, Caroline; Fu, Huazhu (Cham : Springer Nature Switzerland : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the first MICCAI Workshop on Resource-Efficient Medical Image Analysis, REMIA 2022, held in conjunction with MICCAI 2022, in September 2022 as a hybrid event. REMIA 2022 accepted 13 papers from the 19 submissions received. The workshop aims at creating a discussion on the issues for practical applications of medical imaging systems with data, label and hardware limitations.
Multi-Task Semi-Supervised Learning for Vascular Network -- Segmentation and Renal Cell Carcinoma Classification -- Self-supervised Antigen Detection Artificial Intelligence (SANDI) -- RadTex: Learning Effcient Radiograph Representations from Text Reports -- Single Domain Generalization via Spontaneous Amplitude Spectrum Diversification -- Triple-View Feature Learning for Medical Image Segmentation -- Classification of 4D fMRI Images Using ML, Focusing on Computational and Memory Utilization Effciency -- An Effcient Defending Mechanism Against Image Attacking On Medical Image Segmentation Models -- Leverage Supervised and Self-supervised Pretrain Models for Pathological Survival Analysis via a Simple and Low-cost Joint Representation Tuning -- Pathological Image Contrastive Self-Supervised Learning -- Investigation of Training Multiple Instance Learning Networks with Instance Sampling -- Masked Video Modeling with Correlation-aware Contrastive Learning for Breast Cancer Diagnosis in Ultrasound -- A self-attentive meta-learning approach for image-based few-shot disease detection -- Facing Annotation Redundancy: OCT Layer Segmentation with Only 10 Annotated Pixels Per Layer.
Keywords: Image processing-Digital techniques; Computer vision; Artificial intelligence; Education-Data processing; Social sciences-Data processing; Computer Imaging, Vision, Pattern Recognition and Graphics; Artificial Intelligence; Computers and Education; Computer Application in Social and Behavioral Sciences